Regulation of BCR-dependent germinal center B-cell formation by HGAL and insight into its emerging myeloid ortholog, C1ORF150 - Toran, Paul; Novelli, Anthony; Lazor, Jennifer; Vachon, Alexandra; Wojchowski, Don M. (Frontiers in Immunology, 2024)
The specificity of cytokine and immuno receptor signaling frequently depends upon receptor recruitment of select adaptor proteins, and specifically engaged effectors. This review focuses on the orthologous adaptor proteins, HGAL and C1ORF150, and aims to provide insight into their respective modulation of lymphoid and myeloid cell signaling, formation, and function. HGAL acts predominantly within germinal center B-cells as an important BCR signal transducer. Effects on BCR signalosome assembly involve HGAL's localization to the plasma membrane via its lipidation; initial interactions with SYK; the pY-phosphorylation of HGAL including its recruitment of GRB2; and HGAL engagement of PDZ-RhoGEF and RhoA signaling. At ligated BCR's, this includes HGAL(-GRB2) stimulation of SYK kinase; attenuation of calcium flux-dependent and NF-κB expression; promotion of cSMAC formation; and cytoskeletal remodeling as associated with HGAL-attenuated cell migration. HGAL and partnered effectors also impact on DLBCL pathogenesis, and studies are summarized on HGAL's actions (using DLBCL and Burkitt lymphoma B-cells) including cell migration effects; HGAL modulation of cytoskeletal components; and insightful HGAL transgenic mouse and xenograft models. For C1ORF150, its HGAL-homologous subdomains are considered, together with studies that demonstrate C1OR150's FcεRI-and KIT-mediated expression and phosphorylation in primary human mast cells. Intriguingly, recent GWAS studies have identified a C1ORF150 in-frame splice variant that is strongly associated with urticaria. Candidate mechanisms via which the encoded "C1ORF150-∆exon2" isoform affects mast cell degranulation are considered, including FcεR1 and/or KIT receptor connections, and candidate "myristoylation switch" mechanisms.